EFFECT OF ARSENIC (As) ON GROWTH AND PHYSIOLOGY OF MAIZE (ZEA MAYS) IN VARYING SOILS - B. Hussain; M. Sanaullah; M. Iqbal; F. Mahmood; F. Azeem; M. Shahid; T. Shahzad; S. Hussain1 (Journal of Animal and Plant Sciences, 2021)
Maize is one of the main fodders and food source and even staple food in different countries. The presence of arsenic (As) in the soil has been reported to affect the growth and productivity of agricultural crops. The plant uptake of As from soil might depend on the composition and type of soil texture. In this study, we assessed the effect of four levels (0, 25, 50 and 100 mg As kg-1 of soil) of As on As uptake as well as the growth and physiology of maize (Zea mays) grown in three soils varying in texture in a pot experiment conducted at Government college university Faisalabad in February-March, 2018. Results revealed that the growth parameters significantly decreased in response to increasing concentrations of As in all three types of soil. The most prominent effects of As treatments on maize were shown under sandy loam soil followed by loamy soil and then clayey soils. At highest level of As application, the maximum As concentration in plant shoot and root were found in sandy loam soil (45.1 and 93.4 mg kg-1) followed by that in loamy soil (39.9 and 86.2 mg kg-1) and clayey soils (34.9 and 81.1 mg kg-1). Similarly, the maximum Diethylenetriamine Pentaacetic Acid (DTPA) extractable As (2.4 mg kg-1) was detected in sandy loam soil, whereas, the lowest (2.1 mg kg-1) was observed in clayey soil. Antioxidant enzyme activities and protein contents were maximum in the soils amended with 25 mg as kg-1, and were significantly decreased in the soils containing higher levels of As. However, these values were relatively higher in the clayey soils followed by the loamy soil and least in the sandy loam soil. The reactive oxygen species (ROS) including hydrogen peroxide (H2O2), superoxide (O2-) and melondialdehyde (MDA) were found to increase with increasing level of As in the soils. The effects of As on ROS were also maximum in sandy loam soil followed by the loamy soil and minimum in clayey soil. Conclusively we can say that the presence of As significantly affected the growth and physiological parameters of the maize crop. However, the effects of As were more severe in sandy loam soil as compared to the other ones.
Keywords: Arsenic; Maize; Soil texture; DTPA extractable As; Growth; Antioxidants